Cloud called bhura : climate champions to the rescue - Vachharajani, Bijal; Aindri C. (ill.) (New Delhi Talking Cub, 2019)
Amni wakes up one morning to find the sky taken over by a huge brown cloud. Where did this cloud appear from suddenly? Even as she and her friends Mithil, Tammy and Andrew start finding out more, their city of Mumbai starts reeling from the changes the cloud brings to the weather. Bhura Cloudus, as the media calls it, contains noxious gases, causes scalding rain to fall, makes birds flee the city, and suffocates every living thing. What will Mota Bhai, the powerful politician, do now? Can Vidisha and Bidisha, the scientist twins, find a solution? And what about superstar Pavan Kumar and the amazing cloud-sucking machine? Can Bhura ever be driven away, or is it already too late? Thought-provoking, funny and inspiring, A Cloud Called Bhura is about the changing global climate and the havoc it can cause, as well as the forces of friendship, trust and community that give hope and will help counter this deadly threat to humanity.
Keywords: English Fiction